Interactive Control System dalam Implementasi Strategi Penyelesaian Masalah Perusahaan - Jolanda, Veronica; Budianto, Yovan (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Management control system is one way the company to establish a strategy and be a system that controls the performance of the company. However, each company has a strategy, problems and way of solving different problems. Interactive Control System is a system that has a positive impact on the formation and implementation of the strategy. Interactive control system is also expected to be one of the ways the company to resolve the problems that exist in the company.